R- and Q-mode multivariate analysis to sense spatial mineralization rather than uni-elemental fractal modeling in polymetallic vein deposits. Issue 4 (4th July 2018) - Darabi-Golestan, F.; Hezarkhani, A.
ABSTRACT: Anomalous patterns from mineralizing processes are very complex associated with their spatial and frequency properties. Determination of how clustering elemental occurrences are and their spatial association within polymetallic veins deposit as a particular geological feature is critical issue for exploration. Fractal (as non-Euclidean geometries) models are uni-elemental and quantitative method, but R-mode and Q-mode analysis corresponding to multivariate techniques could ease quantitative and qualitative interpretations. The R-mode and Q-mode are the two main informative procedures in many multivariate analyses and are useful in order to handle quantitative and qualitative properties. The first and second Dimension of variation from the R-mode and Q-mode analysis explain 77% of the total variance of the polymetallic system at the area. The mineralization trend of Ag≈As≥Au>Pb>Te>Mo>Zn>S>W>Cu indicated from associated large Euclidean distances from R-mode, occurred due to polymetallic samples ID's of 35, 33, 28, 29, 32, 34, 31, 30, 36, 81, 47 and 80 which resulted from Q-mode analysis. The combination of them is introduced by correspondence analysis (CA) intuitive graphical display to sense and respond to spatial heterogeneity of polymetallic vein deposit.